The Popularity of Financial Services on The Fintech Market in Poland and The Problem of Financial Inclusiveness - Marcin SURÓWKA; Katarzyna ŁACH (Communications of International Proceedings, 2021)
The aim of the article was to examine the degree of penetration of Polish society by FinTech enterprises, with particular emphasis on the elderly and people living in the countryside or in small towns. The results of the research suggest that in the case of Poland it is difficult to talk about the inclusive nature of FinTech services, because the elderly and people living far from large cities have not heard about FinTechs at all, or if they have heard, they do not use them. According to Polish Central Bank (Ceglarz (2021)) the same groups of people often do not have a current account at the bank. There are municipalities in Poland where there is not a single ATM. 2.3 million citizens live in such areas (Ceglarz (2021)).
Keywords: FinTech; inclusiveness; Poland